Modular tumor prostheses: are current stem designs suitable for distal femoral reconstruction? : a biomechanical implant stability analysis in Sawbones - Bischel, Oliver E.; Nadorf, Jan; Klein, Simon Benjamin; Gantz, Simone; Kretzer, Jan Philippe (Archives of orthopaedic and trauma surgery, 2019)
Introduction: High loosening rates after distal femoral replacement may be due to implant design not adapted to specific anatomic and biomechanical conditions. Materials and methods: A modular tumor system (MUTARS®, Implantcast GmbH) was implanted with either a curved hexagonal or a straight tapered stems in eight Sawbones® in two consecutively generated bone defect (10 cm and 20 cm proximal to knee joint level). Implant-bone-interface micromotions were measured to analyze main fixation areas and to characterize the fixation pattern. Results: Although areas of highest relative micromotions were measured distally in all groups, areas and lengths of main fixation differed with respect to stem design and bone defect size. Regardless of these changes, overall micromotions could only be reduced with extending bone defects in case of tapered stems. Conclusions: The tapered design may be favorable in larger defects whereas the hexagonal may be advantageous in defects located more distally.
Gesehen am 17.06.2019